Impact of Virtual Reality Technology on Pain and Anxiety in Pediatric Burn Patients: A Systematic Review and Meta-Analysis - Smith, Kathryn L.; Wang, Yang; Colloca, Luana (Frontiers in Virtual Reality, 2022)
Introduction. Virtual reality (VR) has the potential to lessen pain and anxiety experienced by pediatric patients undergoing burn wound care procedures. Population-specific variables require novel technological application and thus, a systematic review among studies on its impact is warranted. Objective. The objective of this review was to evaluate the effectiveness of VR on pain in children with burn injuries undergoing wound care procedures. Methods. A systematic literature review was performed using PubMed and CINAHL databases from January 2010 to July 2021 with the keywords “pediatric,” “burn”, “virtual reality,” and “pain.” We included experimental studies of between- and within-subjects designs in which pediatric patients’ exposure to virtual reality technology during burn wound care functioned as the intervention of interest. Two researchers independently performed the literature search, made judgements of inclusion/exclusion based on agreed-upon criteria, abstracted data, and assessed quality of evidence using a standardized appraisal tool. A meta-analysis was conducted to evaluate the effectiveness of the VR on burning procedural pain in pediatric population. Standard mean difference (SMD) was used as an index of combined effect size, and a random effect model was used for meta-analysis. Results. Ten articles published between January 2010 and July 2021 passed the selection criteria: six randomized controlled trials and four randomized repeated-measures studies. Consistent results among the studies provided support for VR as effective in reducing pain and potentially pain related anxiety in children undergoing burn wound care through preprocedural preparation (n=2) and procedural intervention (n=8). A random effects meta-analysis model indicated a moderate and significant combined effect size (SMD= 0.60, 95% CI= 0.28-0.93, p= 0.0031) of VR effects on pain intensity ratings with no significant heterogeneity of VR intervention effects between studies. Only one study reported direct influence of VR intervention on pre-procedural situational anxiety with a moderate effect size (Cohen’s d=0.575, 95%CI=0.11-1.04). Conclusions. Children’s exposure to VR during burn care procedures was associated with lower levels of pain and pain related anxiety. Moderate to large effect sizes support the integration of VR into traditional pediatric burn pain protocols irrespective of innovative delivery methods and content required for use in burned pediatric patients.